Association between diabetes or antidiabetic therapy and lung cancer: A meta‐analysis. Issue 6 (15th July 2013) - Wang, Zhida; Bao, Cuiping; Su, Cheng; Xu, Weili; Luo, Hongbin; Chen, Liming; Qi, Xiuying
Abstract Aims/Introduction Diabetes can increase the risk of cancers at several sites, but the association between diabetes and lung cancer remains unclear. We aimed to provide the quantitative estimates for the association between diabetes or antidiabetic treatment and lung cancer risk in the present meta‐analysis. Materials and Methods Cohort studies were identified by searching the PubMed database (January 1960 through October 2012) and manually assessing the cited references in the retrieved articles. Study‐specific relative risks (RRs) and 95% confidence intervals (CIs) were estimated using a random‐effects model. Study quality was assessed using the Newcastle–Ottawa scale. Results A total of 19 cohort studies were included in the present meta‐analysis. Of these, 14 studies focused on the association between diabetes and lung cancer incidence, and seven studies focused on the association between antidiabetic treatment and lung cancer incidence. Compared with non‐diabetic individuals, diabetic patients do not have an increased risk of lung cancer (RR = 1.04, 95% CI 0.87–1.24). The association between diabetes and lung cancer remained not statistically significant in subgroup analysis stratified by study characteristics, study quality, diabetes ascertainment or important confounders. A null association between insulin or biguanides therapy and lung cancer risk was found. However, the diabetic patients receiving thiazolidinedione (TZD) treatment had a 20% reduced risk of lung cancer than those without TZD treatment. Conclusions No association between diabetes and lung cancer risk was found. However, TZD treatment might reduce lung cancer risk in diabetic patients.